Educational attainment of second generation Hmong in a rural ethnic enclave - Paiva, Marianne Christine (Kansas State University, 2016)
This study investigates the role of second-generation Hmong in South Oroville in order to better understand broader questions of racial and ethnic integration among immigrants in rural areas of the U.S., the role of education in rural community viability, and the sustainability of rural communities with population growth derived mainly from immigration. I focus on two fundamental questions: Why are second-generation Hmong in South Oroville exceeding expectations for educational attainment, despite high levels of poverty and low levels of first generation educational attainment? How do second generation Hmong in South Oroville use their education? I draw on 16 qualitative interviews with second generation Hmong Americans in South Oroville to explore these questions. There are two key findings. First, the high college attainment rate was due to a high level of social integration with strong social ties within their networks, unique bridging through Upward Bound between the dominant society and the Hmong population, high parental expectations and high sibling expectations of educational attainment, and high amounts of financial support from grants and work study facilitated a 70% college attainment rate in 18-24 year olds in the population. Second, the Carr-Kefalas brain drain theory did not fully explain the post-education pathways for this population. An alternative theory of post-education pathways called the Hmong Typology explains post-education as dependent on gender expectations and sibling obligation.
Keywords: Hmong; Educational attainment; Immigration; Rural enclave